2010
DOI: 10.1056/nejmoa0907929
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone, Vitamin E, or Placebo for Nonalcoholic Steatohepatitis

Abstract: BACKGROUND-Nonalcoholic steatohepatitis is a common liver disease that can progress to cirrhosis. Currently, there is no established treatment for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

63
2,597
6
103

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 2,774 publications
(2,769 citation statements)
references
References 30 publications
63
2,597
6
103
Order By: Relevance
“…More recently, the dual PPARα/δ agonist elafibranor (GFT505) achieved improvement in steatohepatitis without fibrosis worsening in patients with a NAS score ≥4 and decreased fibrosis in the subgroup of patients with NASH who responded to GFT505 47. PPARγ activation by pioglitazone significantly improves steatosis, ballooning, and inflammation as well as metabolic markers in patients with NASH after 6 or 12 months of treatment 48. A recent 18‐month study in prediabetic and diabetic patients with biopsy‐proven NASH demonstrated that pioglitazone was well tolerated without adverse effect and was associated with long‐term metabolic and histologic improvement 33.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the dual PPARα/δ agonist elafibranor (GFT505) achieved improvement in steatohepatitis without fibrosis worsening in patients with a NAS score ≥4 and decreased fibrosis in the subgroup of patients with NASH who responded to GFT505 47. PPARγ activation by pioglitazone significantly improves steatosis, ballooning, and inflammation as well as metabolic markers in patients with NASH after 6 or 12 months of treatment 48. A recent 18‐month study in prediabetic and diabetic patients with biopsy‐proven NASH demonstrated that pioglitazone was well tolerated without adverse effect and was associated with long‐term metabolic and histologic improvement 33.…”
Section: Discussionmentioning
confidence: 99%
“…A large RCT of patients with NASH without diabetes demonstrated that, compared to placebo, pioglitazone 30 mg daily for 96 weeks was associated with improvement in histology and higher rates of NASH resolution 19. More recently, the effects of pioglitazone on NASH in patients with prediabetes and T2D were evaluated 20.…”
Section: Nafld/nash‐specific Therapiesmentioning
confidence: 99%
“…8 Longer treatment (>1 year) might not result in a more marked reduction of ALT. 25,26 Histological Response (Table 2) Steatosis. All but one 27 trials showed a reduction in steatosis higher than placebo.…”
Section: Efficacy Outcomesmentioning
confidence: 99%
“…However, individual response was variable with only 47%-65% of patients experiencing reduction in steatosis. 21,22,26,28 Importantly, the magnitude of reduction is usually not reported. With rosiglitazone it was 20%, ranging from 30%-60% in responders.…”
Section: Efficacy Outcomesmentioning
confidence: 99%